2009
DOI: 10.1007/s10549-009-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Both t-Darpp and DARPP-32 can cause resistance to trastuzumab in breast cancer cells and are frequently expressed in primary breast cancers

Abstract: The clinical use of trastuzumab (Herceptin), a humanized antibody against the HER2 growth factor receptor, has improved survival in patients with breast tumors with ERBB2 amplification and/or over-expression. However, most patients with advanced ERBB2 amplified breast cancers whose tumors initially respond to trastuzumab develop resistance to the drug, leading to tumor progression. To identify factors responsible for acquired resistance to trastuzumab, gene expression profiling was performed on subclones of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 20 publications
5
81
1
Order By: Relevance
“…3 Recent studies have shown that DARPP-32 promotes cancer cell survival, drug resistance and invasion. [5][6][7][8][9] However, the mechanisms that regulate DARPP-32 expression and promote gastric carcinogenesis remain unclear. Infection with Helicobacter pylori has been classified by the WHO as a group 1 carcinogen 10 and considered a major risk factor for the development of gastric cancer.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…3 Recent studies have shown that DARPP-32 promotes cancer cell survival, drug resistance and invasion. [5][6][7][8][9] However, the mechanisms that regulate DARPP-32 expression and promote gastric carcinogenesis remain unclear. Infection with Helicobacter pylori has been classified by the WHO as a group 1 carcinogen 10 and considered a major risk factor for the development of gastric cancer.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…All of these results suggest that T39 phosphorylation plays an important role in t-Darpp’s capacity to modulate PKA activity. This same site has already been shown to be critical for t-Darpp’s ability to activate EGFR signaling [21], to cause sustained Akt phosphorylation and to confer trastuzumab resistance [17], perhaps suggesting that these outcomes are downstream effects of t-Darpp-mediated PKA stimulation.…”
Section: Discussionmentioning
confidence: 86%
“…Darpp-32 inhibits PP1 via a protein-protein interaction that requires the N-terminal domain that is absent from t-Darpp, but the molecular mechanism by which Darpp-32 inhibits PKA is not known. We focused on the T39 phosphorylation site in t-Darpp because phosphorylation at this site is required for t-Darpp’s ability to increase trastuzumab resistance and PI3K/Akt signaling [17,21] and phosphorylation at the analogous T75 site in Darpp-32 converts Darpp-32 from a PP1 inhibitor into a PKA inhibitor [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of both DARPP32 and t-DARPP led to increased phosphorylation of Akt and increased BCL2 protein levels in trastuzumab-resistant cell lines 79 and in vivo. 80 Moreover, t-DARPP contributes to trastuzumab resistance by blocking Abbreviations: HER2, human epidermal growth factor receptor 2; NK, natural killer; FcγR, fragment crystallizable region gamma receptor; Src, Rous sarcoma tyrosine kinase; PTEN, phosphatase and tensin homolog; PI3K, phosphatidylinositol 3-kinases; Akt, serine/threonine protein kinase; mTor, mammalian target of rapamycin; DARPP-32, dopamine-and cyclic-AMP-regulated phosphoprotein; t-DARPP, truncated form of dopamine-and cyclic-AMP-regulated phosphoprotein; MMP9, matrix metallopeptidase 9; p95, truncated form of HER2; Muc4, mucin 4; IGF-1R, insulin-like growth factor receptor 1; Met, hepatocyte growth factor receptor. …”
Section: Milani Et Almentioning
confidence: 99%